2020
DOI: 10.1021/acsomega.0c01864
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Magnetic Nanoflowers as an Effective Nanozyme and Antimicrobial Agent for Biosensing and Catalytic Reduction of Organic Dyes

Abstract: Mussel-inspired chemistry has been embodied as a method for acquiring multifunctional nanostructures. In this research, a novel mussel-inspired magnetic nanoflower was prepared through a mussel-inspired approach. Herein, magnetic PDA–Cu nanoflowers (NFs) were assembled via incorporating magnetic Fe 3 O 4 @SiO 2 –NH 2 core/shell nanoparticles (NPs) into mussel-inspired polydopamine (PDA) and copper phosphate as the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Figure reveals that the degradation of all MNPCuNFs was strongly dependent on where k abs is the observed rate constant of a pseudo-first-order reaction (min –1 ) and can be calculated from the slope of the line by plotting ln­( C / C 0 ) versus t (min –1 ). Plots of ln­( C / C 0 ) versus t (min –1 ) were linear with high correlation coefficients, R 2 > 0.9, establishing that the degradation rate of RhB by MNPCuNFs fits a pseudo-first-order kinetics model, which agrees with previous findings on the degradation of MB using polydopamine copper phosphate nanoflower . The removal of RhB using MNPCuNFs (bare MNP) and MNPCuNFs with surface-functionalized MNPs was investigated to determine their efficiencies.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure reveals that the degradation of all MNPCuNFs was strongly dependent on where k abs is the observed rate constant of a pseudo-first-order reaction (min –1 ) and can be calculated from the slope of the line by plotting ln­( C / C 0 ) versus t (min –1 ). Plots of ln­( C / C 0 ) versus t (min –1 ) were linear with high correlation coefficients, R 2 > 0.9, establishing that the degradation rate of RhB by MNPCuNFs fits a pseudo-first-order kinetics model, which agrees with previous findings on the degradation of MB using polydopamine copper phosphate nanoflower . The removal of RhB using MNPCuNFs (bare MNP) and MNPCuNFs with surface-functionalized MNPs was investigated to determine their efficiencies.…”
Section: Resultssupporting
confidence: 87%
“…Plots of ln(C/C 0 ) versus t (min −1 ) were linear with high correlation coefficients, R 2 > 0.9, establishing that the degradation rate of RhB by MNPCuNFs fits a pseudo-first-order kinetics model, which agrees with previous findings on the degradation of MB using polydopamine copper phosphate nanoflower. 24 The removal of RhB using MNPCuNFs (bare MNP) and MNPCuNFs with surface-functionalized MNPs was investigated to determine their efficiencies. At 50 °C, >90% of RhB was removed by MNPCuNFs (k abs = 0.2736) within 10 min, while <60% (k abs < 0.13) was degraded for MNPCuNFs with surface-functionalized MNPs (Figure 4a), which can be attributed to the Fenton active sites on the bare MNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic nanozymes, such as mussel‐inspired nanoflower (PDA‐Cu NFs) are considered as antibacterial agents for biosensing applications. [ 130 ] Another group reported laccase‐like active magnetic nanozyme which can be used for efficient removal of toxic phenolic pollutant like o ‐phenylenediamine (OPD). [ 131 ] Optically active plasmonic nanozymes (AuNPs) exhibits enhanced peroxidase‐mimicking activity.…”
Section: Nanozymesmentioning
confidence: 99%
“…Moreover, the catalytic activity of the synthesized CM@SS-BBTU-Cu(II) catalyst was compared with those of some heterogeneous catalysts 33,[119][120][121][122][123][124][125][126][127][128][129][130] recently used in the reduction of MB in order to show the advantage of our catalyst system (Table 3). The results showed that CM@SS-BBTU-Cu(II) was better than previously reported catalysts in terms of reaction time.…”
Section: Reduction Of 4-npmentioning
confidence: 99%